Structure of the coral and octocoral communities of Isla de Aves, Venezuela, Northeast Caribbean - Yranzo, A. (2014)
The Isla de Aves Wildlife Refuge is the northernmost portion of the Venezuelan territory generating 135 000km2 of Exclusive Economic Zone. Studies on coral communities are scarce and old (1970s), due to its location 650km northeast of La Guaira Port and because it has military facilities. To upgrade baseline information we estimated size structure, percent live cover, species composition and abundance of corals and octocorals. We evaluated 16 sites around the island using the AGRRA Protocol (band-transects 10 m2) between 1.5 and 21m depth (n=67 transects), and visual surveys conducted in other five sites. We recorded 2 327 colonies belonging to four hydroid species and 36 species of stony corals in 11 families. The values for diversity, dominance and evenness of the coral community ranged between 0.78 and 2.12 (SW), 0.15 and 0.61 and 0.57 y 0.92 respectively. Most coral species had relative abundance values under 3%, except Porites astreoides (25.57%), Pseudodiploria strigosa (18.22%) and Siderastrea siderea (14.44%). They were represented mostly by smaller colonies, between 3 and 30cm in maximum diameter and between 0 and 5cm high. A total of 13 octocoral species belonging to three families were identified. Pseudopterogorgia americana was the most abundant species. The mean percent of live coral (including hydrocorals) was 22.30% (SE=1.73) (15.45% for dead coral, SE=3.28). Dead coral had the highest percentage of dissimilarity between sites (9.21%) (ANOSIM) and 16.57% contribution (SIMPER analysis). Octocoral live cover ranged from 0 to 21.35% with a mean of 6.38% (SE=0.99). Research on benthic communities of Isla de Aves should continue, especially in the deeper areas, to assess ecological conditions. Rev. Biol. Trop. 62 (Suppl. 3): 115-136. Epub 2014 September 01.